Relationship Between Knowledge Of Mothers Of Toddlers And Behavior To Prevent Recurrent Pneumonia At Southeast Sulawesi Province - Islaeli, Islaeli; Nofitasari, Ari; Astri, Astri (PT. Nursing Genius Care, 2024)
Background: Pneumonia causes more deaths in children under five than AIDS, malaria and measles combined. If toddlers is not handled and cared for properly, pneumonia can recur or be called recurrent pneumonia. Based on initial data collection for the last 3 months, the number of cases of recurrent pneumonia in toddlers in the Bahteramas Hospital Poly room in 2022 was 36 cases. Purpose: This study was to determine whether there is a relationship between the knowledge of mothers under five and the behavior of preventing recurrent pneumonia at Bahteramas General Hospital, Southeast Sulawesi Province. Methods: research used is quantitative research. The design used in this study is a correlational analytic study using a cross sectional study approach. The total population in this study was 36 respondents with a total sample of 33 respondents. Results: The results of statistical tests using the chi-square test obtained a p value of 0.000 which is less than α (0.05) meaning that there is a relationship between knowledge and behavior to prevent recurrent pneumonia. Conclusion: This study found a significant relationship between the knowledge of mothers with toddlers and the behavior of preventing recurrent pneumonia at Bahteramas General Hospital, Southeast Sulawesi Province. Education for mothers with toddlers is essential to enhance efforts to prevent recurrent pneumonia in their children.